Chose the wrong guy, gave him the wrong finger [compact disc, unabridged] - Harbison, Elizabeth M. (Macmillan Audio, 2013)
At twenty-one, Ashley Barton was on her way to the alter to marry Burke Morrison, her high school sweetheart, when something derailed her. Rather, someone derailed her--another man who begged her right up to the last minute to reconsider the marriage, because he loved her more. Besides, the other man told her, Burke had been cheating on her. For a long time. His argument was compelling, and Ashley wrestled with the obligation of fulfilling her guests' expectations--providing a wedding--and running for her life.